2011
DOI: 10.1016/j.applthermaleng.2011.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of two phase laminar mixed convection nanofluid in elliptic ducts

Abstract: Laminar mixed convection Al 2 O 3-Water nanofluid flow in elliptic ducts with constant heat flux boundary condition has been simulated employing two phase mixture model. Threedimensional Navier-Stokes, energy and volume fraction equations have been discretized using the finite volume method. The Brownian motions of nanoparticles have been considered to determine the thermal conductivity and dynamic viscosity of Al 2 O 3-Water nanofluid, which depend on temperature. Simulation effects of solid volume fraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, in the liquid-solid two-phase flow, the viscosity and density of the nanoparticle should be at least of the same order of magnitude as those of liquid phase, or even higher, which is confirmed in the following section. Equation (16) cannot be simplified as Miller did, which directly indicates that the traditional empirical correlation based on gas-solid circulating fluidized bed is not appropriate for the viscosity calculation of nanoparticles.…”
Section: Nanoparticle Viscosity Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in the liquid-solid two-phase flow, the viscosity and density of the nanoparticle should be at least of the same order of magnitude as those of liquid phase, or even higher, which is confirmed in the following section. Equation (16) cannot be simplified as Miller did, which directly indicates that the traditional empirical correlation based on gas-solid circulating fluidized bed is not appropriate for the viscosity calculation of nanoparticles.…”
Section: Nanoparticle Viscosity Modelmentioning
confidence: 92%
“…There are commonly four popular approaches for numerically studying nanofluids: the single-phase model [6,7], the mixture multiphase model [8][9][10][11][12][13][14][15][16][17][18][19][20][21], the EulerianEulerian multiphase model [22][23][24][25][26][27] and the Euler-Lagrange multiphase model [28][29][30][31]. Although a variety of modified models that describe the heat transfer process in nanofluids is continually presented, thus far all modeling results are not very satisfactory: they all underestimate heat transfer coefficients when compared with experiment.…”
Section: Introductionmentioning
confidence: 99%
“…They further investigated the laminar flow in a curved duct of elliptical cross-section with fins and found the heat transfer rate is the maximum with the same aspect ratio [25]. However, Shariat et al [26] numerically calculated the Nusselt number of laminar mixed convection in elliptic channels with a constant heat flux boundary condition, and found that the best heat transfer performance appears when the aspect ratio is 0.75. The difference may be ascribed to the different thermal boundary conditions and the nanofluid chosen as the working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent forced convection heat transfer of water and nanofluid inside tube under single phase approach was carried out by [2][3][4][5][6]. Pak and Cho [7] were investigated the effect of two different metallic oxide particles, TiO 2 , and Al 2 O 3 , with mean diameters of 27 nm and 13inm, respectively, on base fluid (water) experimentally.…”
Section: Introductionmentioning
confidence: 99%